La inclusión educativa en el proceso enseñanza aprendizaje en el sexto y séptimo grado de la Escuela “Federación Deportiva de Cotopaxi”, año lectivo 2016-2017. - Escudero Pacheco, Fanny Silvana (2018)
The study of the Educational Exclusion of boys and girls, aims to raise the level of educational inclusion, through a workshop in which is known the optimal methodological strategies for educative inclusion, which help in the teaching-learning process. This workshop is applied to teachers, parents and students. When we are talking about inclusion, we are involving changes and modifications in the contents, methodological strategies, didactic resources, in the same way we must give importance to the formation of values such as respect, solidarity and tolerance, therefore it has been considered convenient to start from a brief account of the legal framework of educational inclusion and its characteristics, to then emphasize the role, values and competencies that all members of the educational community must acquire and perform, and in a primary way, the teacher, since he is the one who is under obligation to respond to the necessities, interests and of its students. This work achieved a great social impact in children with learning problems as it helps them to improve the quality of life by feeling active members of the institutions. The beneficiaries of this work are children who need to be included in education, as well as parents and the entire educational community.